KORELASI WORK LIFE BALANCE DENGAN TURNOVER INTENTION PADA PERAWAT - Ibrahim, Mochammad Malik; Risna Zubaidah; Sagita Candra Puspitasari (Rena Cipta Mandiri, 2025)
Turnover intention among healthcare workers is a global issue that significantly impacts the quality of hospital services. This study aims to analyze the relationship between work-life balance (WLB) and turnover intention among nurses at Masyithoh Bangil Islamic Hospital in 2025. The study design used a quantitative analytical method with a cross-sectional approach. The population consisted of 81 nurses, with a sample of 67 respondents selected through a purposive sampling technique. The research instrument was a standardized questionnaire, while data analysis was conducted using the Spearman correlation test. The results showed that most respondents had a moderate level of WLB (67.2%) and a moderate level of turnover intention (76.6%). The Spearman correlation test produced a p-value of 0.000 (<0.01) with a correlation coefficient of -0.442, indicating a negative relationship with moderate strength. This means that the higher the quality of work-life balance, the lower the turnover intention of nurses. These findings emphasize the importance of managerial efforts to improve nurse welfare through rational workload policies, schedule flexibility, and psychosocial support to reduce the risk of turnover.